A systematic review of migrant women's experiences of successful exclusive breastfeeding in high‐income countries - Chieko Izumi; Joshua Trigg; Jacqueline H. Stephens (Maternal and Child Nutrition, 2024)
Abstract The World Health Organisation recommends exclusive breastfeeding for the first 6 months after childbirth. However, since breastfeeding is influenced by cultural practice, it differs between migrant mothers and nonmigrant mothers. This systematic review examined migrant mothers' perceptions and experiences impacting achievement of exclusive breastfeeding after immigration from a low‐middle‐income country to a high‐income country. CINAHL, Medline, Scopus, Web of Science, PsycINFO and Emcare were searched for qualitative studies published from 2010 to August 2022. Eleven studies met inclusion criteria. We used meta‐ethnographic synthesis to identify overarching themes, resulting in five themes: Migrant mothers (1) ‘recognised the differences in breastfeeding practice between their home and host country’. During acculturation, mothers modify or stick to their breastfeeding practice in their host country based on their (2) ‘breastfeeding knowledge’ by combining their (3) ‘original ethnic identity’ with the (4) ‘influence of family members, healthcare workers, infants, peers and workplace’. Although they face barriers, their (5) ‘autonomy’ motivated them to continue breastfeeding in a country where the breastfeeding norm differs from where they come from. Intrapersonal and interpersonal socio‐ecological factors played a significant role in their breastfeeding practice in the host country. Findings indicate public health policy and practice to support breastfeeding for migrant women in high‐income countries can be improved, particularly by emphasising the importance of providing affirmative, comprehensive and practical support from healthcare professionals.